A novel anode catalyst layer with multilayer and pore structure for improving the performance of a direct methanol fuel cell. (30th May 2012) - Liu, Guicheng; Wang, Meng; Wang, Yituo; Tian, Zhe; Wang, Xindong
SUMMARY: A novel anode catalyst layer (CL) has been prepared by ultrasonic‐spray process which combines directly spraying method and catalyst‐coated membrane switchover method, and heated‐stereoscopic process has been used to enhance bond force between CLs and proton exchange membrane in this paper. The scanning electron microscopy, electrochemical impedance spectra and polarization curves show that: the anode outer CL with pores and meshwork structure has increased the electrochemical active surface area and retained the transfer of protons and electrons, and the anode inner CL with compact structure has prevented methanol crossover. And the gradient catalysis for methanol electrochemical catalytic oxidation reaction has been achieved. The open circuit voltage has reached 0.697 V, and the performance has increased from 116.8 mW cm −2 of traditional membrane electrode assembly (MEA) to 202.6 mWcm −2 of novel MEA at 80°C. Copyright © 2012 John Wiley & Sons, Ltd.